2016
DOI: 10.1007/s00535-016-1166-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice guidelines for peptic ulcer disease 2015

Abstract: The Japanese Society of Gastroenterology (JSGE) revised the evidence-based clinical practice guidelines for peptic ulcer disease in 2014 and has created an English version. The revised guidelines consist of seven items: bleeding gastric and duodenal ulcers, Helicobacter pylori (H. pylori) eradication therapy, non-eradication therapy, drug-induced ulcer, non-H. pylori, non-nonsteroidal anti-inflammatory drug (NSAID) ulcer, surgical treatment, and conservative therapy for perforation and stenosis. Ninety clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 134 publications
(141 reference statements)
1
102
0
16
Order By: Relevance
“…30 In upper gastrointestinal bleeding, a Japanese guideline and another meta-analysis reported that the risk of peptic ulcer complications increases when NSAIDs are given with steroids or anticoagulants. 2,31 We confirmed this effect in relation to small-bowel overt bleeding. NSAIDs induce small-bowel injuries, and other antithrombotic drugs, such as thienopyridine, or steroids, might exacerbate the injury or impair tissue repair and potentially induce small-bowel overt bleeding.…”
supporting
confidence: 68%
“…30 In upper gastrointestinal bleeding, a Japanese guideline and another meta-analysis reported that the risk of peptic ulcer complications increases when NSAIDs are given with steroids or anticoagulants. 2,31 We confirmed this effect in relation to small-bowel overt bleeding. NSAIDs induce small-bowel injuries, and other antithrombotic drugs, such as thienopyridine, or steroids, might exacerbate the injury or impair tissue repair and potentially induce small-bowel overt bleeding.…”
supporting
confidence: 68%
“…Although not yet recommended by the international guideline (10) and the latest guidelines in Japan (20,21), the usefulness of non-contrast and contrast CT for UGIB has also been shown (22).…”
Section: Discussionmentioning
confidence: 99%
“…1,7 In addition, because concurrent H. pylori infection slows the rate of peptic ulcer healing, 8 concurrent infection, and its eradication, might affect the healing rate of post-ESD ulcers. 9,10 We showed that reduction rates at 2 weeks post-ESD in …”
Section: Sirsmentioning
confidence: 99%